(untitled) (Modern education and development, 2024)
This article describes the opening, collection and operation of public libraries in the cities of New Osh, Margilan, Skobelev, Kokand, Namangan, established in accordance with the Resolution of the Fergana regional administration No. 421 of 1898 «On the opening of public libraries and reading rooms in regional and city centers.» information is available. In preparing the article used the documents of the National Archive of Uzbekistan I-19 Fund, Volume 1167. В статье рассказывается об открытии, формировании и работе публичных библиотек в городах Ош, Новый Маргилан, Скобелев, Коканд, Наманган, созданных в соответствии с постановлением Ферганской областной администрации за № 421 от 1898 года «Об открытии публичных библиотек и читальных залов в областных и городских центрах». Статья основана на документах Национального архива Узбекистана, фонд I-19, том 1167.